HUBUNGAN GENDER DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV PADA MATA PELAJARAN IPS DI SEKOLAH DASAR KELURAHAN PEGADUNGAN - Fitria Hamidah; Yustia Suntari; Prayuningtyas Angger W (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the relationship between gender and learning motivation with critical thinking skills among fourth-grade students in Social Studies (IPS) at elementary schools in Pegadungan Urban Village. The background of this research is based on the importance of critical thinking as a 21st-century skill that students must possess, particularly in understanding and analyzing social phenomena discussed in Social Studies. This research employed a quantitative approach using a correlational method. The sample consisted of 106 students selected through disproportionate stratified random sampling from four public elementary schools in Pegadungan. The instruments used included an essay test to measure critical thinking skills and a learning motivation questionnaire developed based on Abraham Maslow's hierarchy of needs theory. The results showed that gender and learning motivation simultaneously had a significant relationship with students’ critical thinking skills, with a multiple correlation coefficient (R) of 0.412 and a coefficient of determination (R²) of 0.169. This indicates that 16.9% of the variance in critical thinking ability can be explained by the combination of gender and learning motivation. The F-test yielded a significance value of 0.000 (< 0.05), indicating that the regression model is statistically significant. Partially, learning motivation had a significant relationship with critical thinking skills, while gender did not. These findings suggest that learning motivation plays a more dominant role in influencing students’ critical thinking skills compared to gender. This research implies that teachers and schools should place greater emphasis on enhancing students’ learning motivation to support the development of their critical thinking abilities.